Soil Quality Attributes in Forest Stands: Influence of Techniques Ecological Restoration - Dalla Valle, Leandro [UNESP]; Castelli, Karen Regina [UNESP]; Barreto, Mariana Gregorio [UNESP]; Laclau, Jean-Paul [UNESP]; Felipe, Marcos Sandro; Silva, Alexandre Marco da [UNESP] (Taylor & Francis Inc, 2019)
Aiming to comprehend the relationship among restoration techniques and soil attributes, we compared the soil attributes of four forest stands: three regarding an experiment initiated eight years ago with distinct techniques: perch, abandonment and transposition, and one that was pristine forest used as a reference. In each local, five soil samples were taken at 0-20 cm, and another sample was taken in a profile (layers: 20-40, 40-60 and 60-80 cm) for analysis of the major physical, chemical and isotopic attributes. The soil density varied from 1.20 to 1.24 g.cm(-3). The different values of chemical attributes among the treatments and reference revealed that the yet the areas are no longer degraded, they cannot be considered restored (reasons explained in the text). Evaluating the characteristics of the soils and making specific silvicultural and soil-related practices before implementing the intervention, is a prerequisite that should be considered by managers in restoration projects.
Keywords: Ecosystem services of soils; forest restoration; soil management; soil quality